Students' meaningful learning experiences from participating in organic chemistry writing-to-learn activities. Issue 2 (22nd January 2021) - Gupte, Trisha; Watts, Field M.; Schmidt-McCormack, Jennifer A.; Zaimi, Ina; Gere, Anne Ruggles; Shultz, Ginger V.
Abstract : Teaching organic chemistry requires supporting learning strategies that meaningfully engage students with the challenging concepts and advanced problem-solving skills needed to be successful. Such meaningful learning experiences should encourage students to actively choose to incorporate new concepts into their existing knowledge frameworks by appealing to the cognitive, affective, and psychomotor domains of learning. This study provides a qualitative analysis of students' meaningful learning experiences after completing three Writing-to-Learn (WTL) assignments in an organic chemistry laboratory course. The assignments were designed to appeal to the three domains necessary for a meaningful learning experience, and this research seeks to understand if and how the WTL assignments promoted students' meaningful learning. The primary data collected were the students' responses to open-ended feedback surveys conducted after each assignment. These responses were qualitatively analyzed to identify themes across students' experiences about their meaningful learning. The feedback survey analysis was triangulated with interviews conducted after each assignment. The results identify how the assignments connected to students' existing knowledge from other courses and indicate that assignment components such as authentic contexts, clear expectations, and peer review supported students' meaningful learning experiences. These results inform how assignment design can influence students' learning experiences and suggest implications for how to support students' meaningful learning of organic chemistry through writing.